(untitled) (KULT_online, 2015)
Andreas Braun’s book analyses the relatively recent phenomenon of rampage shootings at universities. He defines campus shootings as a new hybrid of forms of excessive violence, such as workplace violence and school shootings. Campus shootings, he argues, are a direct result of an ongoing economization of universities that can be observed internationally. While his account of economization and New Public Management is very detailed, Braun fails to convincingly show how the negative effects of the economization can be seen as an explanation for campus shootings. Instead, based on very little data, he constructs rather oversimplifying causal chains in an attempt to explain rampage shootings at universities.